2018
DOI: 10.1038/s41467-018-03646-6
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-ancestry genome-wide association analysis of corneal thickness strengthens link between complex and Mendelian eye diseases

Abstract: Central corneal thickness (CCT) is a highly heritable trait associated with complex eye diseases such as keratoconus and glaucoma. We perform a genome-wide association meta-analysis of CCT and identify 19 novel regions. In addition to adding support for known connective tissue-related pathways, pathway analyses uncover previously unreported gene sets. Remarkably, >20% of the CCT-loci are near or within Mendelian disorder genes. These included FBN1, ADAMTS2 and TGFB2 which associate with connective tissue disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 69 publications
12
85
0
Order By: Relevance
“…Previous work has shown a central role of bone mesenchymal stem cells in osteoblast development (47,48). In addition, SNPs for several corneal traits are also enriched in mesenchymal stem cell peaks, consistent with previously observed enrichment of corneal thickness GWAS SNPs in mesenchymal stem cell/connective tissue cell annotations (49). Results using rat peaks projected into human coordinates largely mirror the human mesenchymal stem cell enrichment findings (Fig.…”
Section: Integration Of Cell-type-specific Atac-seq Peaks With Uk Biosupporting
confidence: 89%
“…Previous work has shown a central role of bone mesenchymal stem cells in osteoblast development (47,48). In addition, SNPs for several corneal traits are also enriched in mesenchymal stem cell peaks, consistent with previously observed enrichment of corneal thickness GWAS SNPs in mesenchymal stem cell/connective tissue cell annotations (49). Results using rat peaks projected into human coordinates largely mirror the human mesenchymal stem cell enrichment findings (Fig.…”
Section: Integration Of Cell-type-specific Atac-seq Peaks With Uk Biosupporting
confidence: 89%
“…COL5A1 mutations are found in classical Ehlers-Danlos Syndrome 50 , which is associated with thinner and steeper corneas 51 . COL5A1 is also a susceptibility locus for central corneal thickness 52,53 . THBS4 encodes an extracellular calcium binding protein that is involved in cell proliferation, adhesion, and migration 54 .…”
Section: Resultsmentioning
confidence: 99%
“…CCT has a strong genetic component, with heritability estimates ranging between 0.68 and 0.95 [11][12][13] . Recently, Iglesias et al 14 reported 44 CCT-genomic regions in a cross-ancestry meta-analysis, including 19 novel loci awaiting independent replication. These 44 CCT-loci account for~8.5% of the variance for this ocular trait.…”
mentioning
confidence: 99%